Determinants of Audit in Manufacturing Companies Listed on the Indonesia Stock Exchange During 2020 - 2023 - Fauzi, Ilham Rizky; Aris, Muhammad Abdul (Jurnal Economic Resource, 2025)
The purpose of this study was to examine the impact of audit tenure, audit fees, client firm size, and public accounting firm (PAF) reputation on audit quality in manufacturing businesses that were listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. regression and secondary data from annual financial reports acquired through documentation procedures, this study took a quantitative approach. Purposive sampling was used to choose the sample, which included 156 manufacturing businesses. The findings showed that audit quality was significantly positively impacted by PAF reputation and audit fees, but not by audit tenure or firm size. The model was able to explain 57.2% of the variation in Audit Quality, according to the Nagelkerke R Square value of 0.572. These findings affirm that the professional reputation of auditors plays a vital role in enhancing audit outcomes. The study’s limitation lies in the scope of variables analyzed, encouraging future research to include factors such as auditor competence and internal control systems. By bolstering empirical evidence regarding the significance of auditor reputation in the Indonesian capital market, this study adds unique value.